Subtle yet encouraging developments: exploring intergroup relations between Arab and Jewish college students over seven years - Sindiani, Mahmood; Hellerstein, Devora; Sky, Bosmat; Ben Zaken, Sigal; Arnon, Michal (Frontiers in Education, 2024)
This study investigates the dynamics of intranational intergroup contact between Arab and Jewish students in a higher education institution in Israel. Guided by the contact hypothesis, the research examines the gap between students' willingness for intergroup closeness and their reported actual intergroup interactions. Using a cross-sectional survey design, quantitative data were collected from a total of 733 Arab and Jewish students at two timepoints: in 2016 (n=419) and in 2023 (n=314). All students were studying to become physical education teachers. The findings revealed both persistent challenges and encouraging trends in intergroup relationships. Despite reported willingness for meaningful connections, the students' reported actual intergroup interactions remained limited. A significant increase in willingness for academic and friendship relationships was observed from 2016 to 2023, suggesting the potential for constructive change. Arab students consistently reported higher willingness for closeness and more frequent interactions than their Jewish counterparts. These findings underscore the importance of structured interventions in higher education settings to foster meaningful intergroup relations, amidst broader societal challenges.